Making Sense of the Emergency Remote Education. Faculty and Students’ Takeaway Lessons from the Pandemic Classroom - Cernicova-Buca, Mariana; Dragomir, Gabriel-Mugurel (Technium Social Sciences Journal, 2022)
The purpose of this paper is to analyse faculty and students’ takeaway lessons from the pandemic classroom, comparing the educational partners’ views on the transition from in-campus to online learning. Data collection was conducted through focus groups to understand the key issues at the level of an educational program, the collected responses being used to highlight the overall perception on the online classes during the pandemic, the most frequently uses online tools, the adaptive strategies to maintain engagement and foster learning and the assessment requirements for completing the 2020-2021 academic year. The results show that while most respondents define the experience as tiresome and complicated, faculty and students alike found enough resources to overcome the challenges and that despite the lack of preparedness for education in times of crisis, the educational process can go on when sufficient effort and commitment are put together. The value of the research is that it brings together faculty and student voices, interpreting a shared experience of the emergency remote education, the findings being useful for preparing educational strategies ensuring the resilience of higher education programs in times of unexpected disruptions.